The Case of Cogtong’s Timori: Features, Usage and Vitality - Rojo, Joshua; Malon, Jake; Fuderanan, Benjean; Deguit, Elenita; Tadena, Lorena (Journal of Interdisciplinary Perspectives, 2024)
Language is a dynamic and ever-evolving entity crafted by human necessity, but its intricacies can fade into obscurity if not meticulously documented and preserved. This case study was employed to gain a deep understanding of the research design inherent in the data, which focuses on exploring the linguistic intricacies of Cogtong's Timori language. This looks into its distinctive features regarding phonology, morphological and lexical blends, and syntax. Through in-depth interviews and observations, key informants shed light on Timori's multifaceted usage, encompassing family, educational, and workplace communication. Additionally, it unveils Timori's historical role as a secret code during World War II, a means for discreetly poking fun at others, and a stealthy language for sharing gossip. Despite its vitality within the Cogtong community, Timori remains confined to this locality, facing a dearth of comprehensive written documentation and formal language promotion efforts. To safeguard this unique linguistic heritage of this community, recommendations are proposed, including the need for comprehensive language documentation, the implementation of bilingual education programs, public promotion initiatives, and advocacy for language policies. Timori's significance lies in its ability to connect people through culture and identity, underscoring the necessity of concerted efforts to ensure its continued vitality for future generations.